Uwarunkowania wspierania MŚP przez samorząd terytorialny w Polsce w świetle prawa subwencyjnego UE - Ignasiak-Szulc, Aranka (The Conditions of Territorial Authorities' Support for SMEs in Poland in the Context of EU Subsidies Control Law, 2005)
Subsidies control law, concerning the possibilities, conditions and procedures of providing the subsidies and other aid to the entrepreneurs from the public funds, is a part of competition policy, which is to create and maintain a system permitting undistorted competition within an economic region.Nowadays in Poland, as in any other Member State, public aid can be provided to the enterprise on approval given by the European Commission. Provisions concerning public aid aimed at SMEs say that this kind of national activity is in principle approved and there is no obligation to notify it to the Commission. Supporting the development of SMEs can be, and should be, one of the instruments of public authorities policy on Polish economy competitiveness improvement.Because of a special role that SME sector plays in the local and regional economy, self governmental authorities should be one of the providers of the development support. In order to subsidize the SMEs sector a wide range of certain instruments can be used by these entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 322-336